Effect of Gamma Radiation and Temulawak Extract (Curcuma xanthorrhiza) on HAART Levels of Mice Mice (Mus musculus) - Septiana K. Sari; Chomsin S. Widodo; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2015)
Gamma radiation can causes cells damage, because the interaction between radiations with cells can produce free radical. The compound that can neutralize and catch free radical is called antioxidant. The objectives of this research were to analyze influence of gamma radiation and Curcuma xanthorrhiza extract to the SGPT level to the mice’s liver. This research uses eighty mices and they were divided into three group, negative control (K-), radiation non extract (R-) and extract plus radiation (R+). The doses of treatment of Curcuma xanthorrhiza extract are 1.4 gr/kg body weight; 2.0 gr/kg body weight; 2.6 gr/kg body weight; 3,2 gr/kg body weight and 3.8 gr/kg body weight, while the exposure of gamma radiation are given during 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes. The measuring of SGPT level in mice’s serum is done by using blood analyzer. The results showed that free radical can damages liver cells and breaks cell wall, so SGPT level in blood to be high. In a row of increasing of Curcuma xanthorrhiza extract dose, then SGPT level to be low.